2015
DOI: 10.17058/reci.v5i1.4898
|View full text |Cite
|
Sign up to set email alerts
|

Índice De Risco Cirúrgico E Infecção De Ferida Operatória Em Puérperas Submetidas a Cesarianas

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The 11.2% SSI occurrence rate found in this study is in accordance to those reported in literature, which varies between 1.53 to 16% [4.11]. Conner et al [2] present in their study a 10.8% rate, while Chianca et al [6] found a 4.1% rate during an evaluation of surgical risk and operative wound infection following C-sections in Belo Horizonte municipality.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The 11.2% SSI occurrence rate found in this study is in accordance to those reported in literature, which varies between 1.53 to 16% [4.11]. Conner et al [2] present in their study a 10.8% rate, while Chianca et al [6] found a 4.1% rate during an evaluation of surgical risk and operative wound infection following C-sections in Belo Horizonte municipality.…”
Section: Discussionsupporting
confidence: 90%
“…In relation to post-discharge surveillance, it is evident the importance of the using and upgrading of this tool, since the mean day of diagnosis was 12 days after operation, with the earliest diagnosis on the fourth day. Studies corroborate this evidence and suggest that such application is essential, in addition to the reinforcement of the surgery site checking by the health care team [5,6].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations